Identification and Functional Analysis of Key Genes Regulating Organic Acid Metabolism in Jujube Fruit - Panpan Tong; Dengyang Lu; Guanglian Liao; Cuiyun Wu; Jiangbo Wang (Agronomy)
Organic acids are crucial indicators of fruit flavor quality, but the metabolic characteristics and regulatory genes of organic acids during jujube fruit development remain largely unexplored. In this study, the cultivar ‘Heigeda’ with a high organic acid content was used as the experimental material. The organic acid content was quantified, and key candidate genes were identified through transcriptome analysis. The results indicated that malic acid and citric acid were the main organic acid content in jujube fruit and increased gradually with fruit development. Transcriptome analysis identified nine genes associated with malic acid and seven with citric acid, with four genes co-regulating malic acid and citric acid. Functional assays by transient overexpression and silencing of these four genes in the jujube fruits revealed that overexpression significantly upregulated the malic and citric acid content. However, only the silencing of aconitase1 (ZjACO1) and aconitase3 (ZjACO3) significantly downregulated the content of malic and citric acids. Therefore, aconitase1 (ZjACO1) and aconitase3 (ZjACO3) are considered the key genes that regulate the metabolism of citric acid and malic acid in jujube fruits. Our study can enrich the regulation mechanism of the organic acid metabolism of jujube fruit and provide theoretical support for the efficient cultivation of jujube fruit.